1960
DOI: 10.1002/aic.690060417
|View full text |Cite
|
Sign up to set email alerts
|

Axial diffusion of liquids in packed beds and end effects

Abstract: Experimental data were obtained on the effect of bed length of packed spheres on axial diffusion coefficients with the frequency response technique used. Lengths of packed section of 6 to 174 cm. were used. The end effects were eliminated by using a novel experimental technique for analyses of the inlet and outlet streams. No effects of length on DL were found.When the end effects were artificially introduced by using void analytical sections a t the two ends, then large effects of length on DL were found. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

1963
1963
2004
2004

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(35 citation statements)
references
References 7 publications
1
34
0
Order By: Relevance
“…by Kurath et al (1999) Kurath et al (1999) Kurath et al (1999) Kurath et al (1999) Schwartz and Smith (1953 Liles and Geankoplis (1960) . Batch specific binary isotherm models (batch # 981015DHC720011 & 990420DHC720067) are plotted................................................................105 Figure 9-3.…”
Section: Estimation Of the Pertechnetate Pore Diffusion Coefficientmentioning
confidence: 99%
See 1 more Smart Citation
“…by Kurath et al (1999) Kurath et al (1999) Kurath et al (1999) Kurath et al (1999) Schwartz and Smith (1953 Liles and Geankoplis (1960) . Batch specific binary isotherm models (batch # 981015DHC720011 & 990420DHC720067) are plotted................................................................105 Figure 9-3.…”
Section: Estimation Of the Pertechnetate Pore Diffusion Coefficientmentioning
confidence: 99%
“…Figure 8-2. Estimation of the impact from end effects and short columns on axial dispersion based on the limited data by Liles and Geankoplis (1960).…”
Section: Column-to-particle Diameter Ratiomentioning
confidence: 99%
“…For the design calculations presented in Chapter 10 these inlet headspaces are modeled as CSTRs whose volumes are 25% of the active bed volumes. Liles and Geankoplis (1960) conducted experiments to ascertain the impact short column lengths and void headspaces have on axial dispersion in packed bed columns. When end effects were eliminated they concluded that no effects of length on axial dispersion were observed.…”
Section: Headspace and Short Column Impactsmentioning
confidence: 99%
“…1, 3,[6][7][8][9]13,15,19,21,24,26 j_n Reynol s num er. There j_s, however, no consensuc~ concerning the absolute magn:i_tud.e of the Peclet number :i.n this J F J8 1 2.,.…”
mentioning
confidence: 99%